Production and Characterization of Andong Bamboo (Gigantochloa pseudoarundinacea (Steudel) Widjaja) Pellets from Various Stem Parts - Wahyu Hidayat; Jacky Michael Pah; Lisman Suryanegara; Udin Hasanudin; Agus Haryanto; Christine Wulandari (The University of Lampung, 2022)
Bamboo is an abundant biomaterial having important potential as a resource for bioenergy development. In this study, the potential of andong (Gigantochloa pseudoarundinacea (Steudel) Widjaja) bamboo for pellet production was evaluated. Some properties of bamboo pellets as density, moisture content, moisture adsorption, compressive strength, and heating value were analysed. The results indicated that bamboo is highly prospective to be explored for fuel pellets commercially. All characteristics of pellet made of bamboo fulfilled the requisites of the commercial pellets. The heating value of the pellets achieved the minimum standard for commercial pellets along with SNI 8675:2018 (>17,5 MJ/kg). The effects of culm parts on the moisture content, density, moisture adsorption were not significant. There were significant differences in compressive strength and heating value between bamboo pellets produced from different culm parts. This research showed potential of andong bamboo pellet for bioenergy resource. Keywords: Andong (Gigantochloa pseudoarundinacea), Biopellet, Mechanical Properties, Physical Properties